Determination of intraparticle diffusivity and fluid-to-solid mass transfer coefficient from single concentration history curve in circulated-type fixed-bed reactor - Noriyoshi Sonetaka; Yoshimi Seida; Takuto Nakano; Eiji Furuya (Adsorption Science & Technology)
In this study, a simple analytical procedure for determining the adsorption kinetic parameters D s and k F from a single concentration history (decay curve) in circulate-type fixed-bed reactor test method was investigated. A simple and reliable method to obtain the parameters D s and k F from the decay curve of circulate-type fixed-bed reactor was developed based on an advanced analytical method for the completely mixed batch reactor test method. The experimental conditions in the circulate-type fixed-bed reactor method that meet the application criteria of the advanced analytical method for the completely mixed batch reactor test method were investigated based on the theoretical decay curves of the test methods. Experimental conditions, such as large liquid–solid ratio Zϕ , short contact time z/u , and small bed height Z , which make the decay behaviors in the circulate-type fixed-bed reactor close to those of the completely mixed batch reactor, were evaluated quantitatively on theoretical basis. Furthermore, the reliability of the adsorption kinetic parameters obtained in this study was verified by comparing the k F values with those from a reported empirical correlation equation for k F .